Validation of a laboratory bench for researching the process of condensation air drying - Prytula, N.; Lyashenko, A. (Energy and Automation, 2025)
The paper presents the results of the validation of a laboratory stand for a recirculation air conditions unit for studying the process of condensation drying. The laboratory stand is installed at the Educational and Research Institute of Atomic and Thermal Power Engineering of Igor Sikorsky Kyiv Polytechnic Institute.The laboratory setup enables the study of key air treatment processes, including mixing, dehumidification, heating, and cooling, for Heating, ventilation, and air conditioning (HVAC) systems in both residential and industrial sectors. It consists of sections for external air supply, air recirculation, a fan and filter, a cooler based on a heat pump, and an electric heater.An automated monitoring system ensures control over parameters such as airflow rate, pressure, temperature, and relative humidity, providing high research accuracy. The developed software allows for flexible operation mode control. The evaluation of the control system's efficiency demonstrated that the modelling corresponds to real processes with an acceptable error of 6%, confirming the high accuracy of the experimental data.The obtained results can be used for further optimization of energy-efficient HVAC system operation modes, contributing to reduced energy consumption and improved environmental sustainability of buildings and industrial facilities, as well as for further research into the process of condensation air drying.Key words: HVAC laboratory stand; energy efficiency; air dehumidification; heat pump